Static analysis of Orifice plate for Different Geometries (International Journal of Engineering and Computer Science, 2017)
Orifice plate is a mechanical element used for measuring rate of flow by restricting flow, hence it is often called a restriction plate. The flow exerts some force on the plate due to impact of jet. The orifice plate acts an as obstacle for the flow. Here in our work we have done static analysis for three different geometries for orifice maintaining net impact area and orifice area same in all three cases. At the end we calculated maximum stress and maximum deformation for all the three geometries of orifice for the assumed working conditions, and found the best geometry which has the minimum stress and minimum deformation.